PERCEPTION OF ADOLESCENTS ON CONTRACEPTIVES: ADVANTAGES, DISADVANTAGES AND METHOD OF USE (Fiep Bulletin - online, 2013)
Descriptive study with a qualitative approach, and action research type, which aimed to identify the perception of adolescents on the advantages and disadvantages and method of use of contraceptives. The study was conducted in a unit of the Family Health Program of the Municipal Health Secretary of Natal / RN. Were surveyed 16 adolescents of both sexes with age ranging from 12 to 16 years, attended the Family Health Unit of Igapó in the city of Natal / RN. We used the field notes and transcripts of speeches during the meetings of the focus group. Among the advantages of contraceptive methods listed by adolescents were: prevent STDs and pregnancy in using the barrier method of condoms; the disadvantages most frequently mentioned by the incorrect use of barrier methods, are pregnancy, acquirement of STDs, no prevention of STD's in hormonal, natural and surgical methods. The adolescents showed consistency between the advantages and disadvantages. Generally, those surveyed showed a good understanding about the use of various contraceptive methods.
Keywords: Adolescent; Contraceptive Methods; Knowledge